The director's craft : a handbook for the theatre - Mitchell, Katie (Routledge, 2009)
The Director’s Craft is a unique and completely indispensable step-by-step guide to directing for the stage. Written by one of the most adventurous and respected directors working today, this book will be an essential item in every student and practitioner’s kitbag. It provides detailed assistance with each aspect of the varied challenges facing all theatre directors, and does so with startling clarity. It will inspire everyone, from the beginner just starting out to the experienced practitioner looking to reinvigorate their practice. Katie Mitchell shares and explains the key practical tools she uses to approach her work with both actors, production teams, and the text itself. She addresses topics such as: the ideas that underpin a play’s text preparing improvizations Twelve Golden Rules for working with actors managing the transition from rehearsal room to theatre analyzing your work after a run has ended. Each chapter concludes with a summary of its critical points, making this an ideal reference work for both directors and actors at any stage of their development.